PERTUMBUHAN DAN HASIL TANAMAN TERUNG AKIBAT PEMBERIAN PUPUK DAUN GANDASIL D DAN ZAT PENGATUR TUMBUH HARMONIK - Jumini Jumini (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2009)
Effect of Gandasil D Fertilizer and Harmonic Growth Regulator on Growth and Yield of Egg Plant Jumini dan Ainun Marliah Fakultas Pertanian Unsyiah, Darussalam Banda Aceh ABSTRACT The aim of this research was to study effect of Gandasil D fertilizer concentration and Harmonik growth regulator on growth and yield of egg plants. Experimental design used was a factorial 3 x 4 with three replications. The two factors investigated were Gandasil D concentration (0 g/l, 2 g/l and 4 g/l of water), and Harmonik growth regulator concentration (0 cc/l, 1 cc/l, 2 cc/l and 3 cc/l of water). Results showed that Gandasil D fertilizer concentration significantly affected length of egg plants and its biomass. The best result of Gandasil D fertilizer was at concentration of 2 g/ l of water. Growth regulator agent concentration showed significant effects on plant height of 30 days and 60 days. The best concentration was 3 cc/ l of water. There was a correlation between Gandasil D fertilizer concentration and Harmonik growth regulator on diameter and length of egg plant.